Fully‐tunable filtering power dividers exploiting dynamic transmission‐zero allocation. Issue 3 (6th December 2016) - Gómez‐García, Roberto; Psychogiou, Dimitra; Peroulis, Dimitrios
Abstract : A new class of Wilkinson‐type power dividers with reconfigurable quasi‐elliptic‐type filtering characteristics is reported. Their design exploits the connection of resonators to the branches of a Wilkinson‐type power divider through impedance inverters that in turn produce power transmission zeros (TZs) at their natural frequencies. In this manner and by making frequency‐controllable these resonators, the created TZs can be tuned to attain an adaptive bandpass‐filtering/power‐division double functionality in terms of centre frequency, passband‐width, and stopband bandwidth/attenuation characteristics. Furthermore, bandstop‐filtering actions can be generated through this technique in wide‐band power divider realisations for the suppression of in‐band interfering signals. Key advantages of the proposed filtering power divider include: unequal transmission‐band spectral widths and out‐of‐band power‐rejection profiles for the transfer functions of the two power‐divider branches, as well as the intrinsic switching‐off of one or both of them. The theoretical foundations of the engineered fully‐tunable filtering power divider and its corresponding RF design guidelines are expounded in this work. In addition, a UHF‐band microstrip prototype is manufactured and characterised for practical‐demonstration purposes.